Renalase: A Novel Molecule of Clinical Importance - Biswas, SK; Akhtaruzzaman, M (Bangladesh Journal of Medical Biochemistry, 2013)
DOI: http://dx.doi.org/10.3329/bjmb.v4i1.13774 Bangladesh J Med Biochem 2011; 4(1): 3